A Study of Quality of Work Life and its association with Job satisfaction among the faculties of higher education institutes - Surange, Sandeep; Luhar, Hiresh; Luhar, Arvind S. (International Journal of Psychosocial Rehabilitation, 2020)
Quality of work Life is one of the most important area of study in HR and Psychology fields. Organizations world over are facing acute retention problems and finding difficult times to cope up with the grave issue of Work satisfaction. Quality of work life plays a pivotal role in ensuring Job satisfaction among employees across the industry including the education field. In this background it was important to conduct a study which tries to establish and analyse the relationship between Quality of work life and Job satisfaction. The present study is an attempt in this direction. For the purpose of the study a survey was conducted by distributing a structured questionnaire to the faculties of various Higher education institutes. The collected responses were analyzed and findings have been presented considering various dimensions.